Re-evaluation of acute erythroid leukemia according to the 2016 WHO classification. (October 2017) - Chen, Yan; Pourabdollah, Maryam; Atenafu, Eshetu G.; Tierens, Anne; Schimmer, Aaron; Chang, Hong
Highlights: The diagnostic criteria for erythroleukemia have been modified. Patients with >20% blasts, of either NEC or ANC, share similar survival outcomes. Cytogenetics remains to be the major risk factor for myeloid neoplasm with EP. Abstract: In the recent update of WHO classification, the definition of myeloid neoplasms with erythroid predominance has been modified shifting the main criteria for calculating blast percentage from non-erythroid cells (NEC) to all nucleated marrow cells (ANC). Thus, the cases previously classified as erythroid/myeloid subtype of acute erythroid leukemia (AEL) based on the 2008 WHO will now be categorized either as myelodysplastic syndrome with excess blasts (MDS-EB) or acute myeloid leukemia, not otherwise specified (AML-NOS). However, the clinical significance of this new classification has not been demonstrated. Thus, we reviewed a leukemia database and reclassified 38 cases previously diagnosed as AEL, erythroid/myeloid subtype, with the consideration of 2016 revision criteria. Twenty seven (71%) of them had >20% blasts in NEC but less than 20% blasts in ANC, and 11 (29%) had >20% in both NEC and ANC. There was no significant difference in overall survivals (OS) among AEL, MDS-EB, and AML-NOS (non-erythroid predominance, NEP). However, AML with myelodysplasia-related changes showed significant shorter OS than AEL, MDS-EB and AML-NOS (NEP). Our results indicate that in myeloid neoplasm with erythroid predominance, patients with >20% blasts, of either NEC or ANC, share similar clinical laboratory features and survival outcomes with AML-NOS.